Interpersonal Communication Strategies in Implementing Character-Based Holistic Education: Strategi Komunikasi Interpersonal Dalam Menerapkan Pendidikan Holistik Berbasis Karakter - Erizki, Yunda Hatma; Rochmaniah, Ainur (Indonesian Journal of Education Methods Development, 2020)
This research explains about how the interpersonal communication strategies of teachers in implementing character-based holistic education in early childhood in RA Insan Mulia school. This study aims to determine the interpersonal communication strategies of teachers in implementing character-based holistic education in PAUD students and determine the inhibiting and supporting factors of interpersonal communication between teachers in PAUD students in implementing character-based holistic education. This study uses a qualitative approach because it is easy for researchers to explore a fact, then provide an explanation related to the reality found. Based on data obtained during the study, the results were found that interpersonal communication strategies are an important part needed by teachers at RA Insan Mulia in implementing character education in the classroom. The strategies used by PAUD teachers at RA Insan Mulia include communication planning, message content, delivery methods and communication barriers. Communication barriers come from the environment of students at home if they do not make habituation and role models like those at school.